A aula de português e as possibilidades de ensino-aprendizagem: um estudo de caso - Luciana Mariz (2009)
In order to better understand how the teaching of the Portuguese Language has been carried out, a Portuguese class was observed in this work, resulting, thus, in a Case Study. Considering that the teaching of the mother language should favor discourse practices and be organized in different axes of reading along with text production, grammar and oraldiscourse, and that the basic unit of teaching is the text, which is materialized in genres, as the Brazilian National Curricular Parameters suggest (PCNs), the observation of class sessions made it possible to verify 1) which text comprehension skills can be developed by thestudents from the tasks assigned in class; 2) which methodologies and which materials give support to the Portuguese lessons; 3) what the students learn when the teachers say they are teaching textual genres; 4) to what extent the grammar exercises lead the students to areflection on the linguistic knowledge, meanwhile backing up the activities of written and oral text comprehension; 5) the concepts of language and language teaching underlined in the tasks assigned in class. The analyses concluded that 1) the reading activities do not concern with decoding skills only, but yet treat this axis of teaching as a mechanical process without exploring the strategies of pre-, while- and post-reading defended by Solé (1998) and Cafiero (2005); 2) the pattern showed when treating the axes perceives language as something static,fixed, homogeneous, not considering interaction and discourse; 3) the traditional and unsystematic treatment given to the study of genres does not help the students to reproduce them effectively; 4) grammar teaching is still not connected with reading and writing practices. The overuse of metalanguage and expressions out of context does not result inepilinguistic activities, centered in the use; 5) oral discourse has not been included as a teaching object yet, although some textbooks offer activities of this axis.